2013
DOI: 10.1103/physrevb.87.235304
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic recombination and absorption in InxGa1xAs/GaAs heterostructure nanowires

Abstract: Photoluminescence (PL), micro-PL, and PL excitation (PLE) spectroscopy for different light polarizations have been used to investigate the electronic properties of GaAs characterized by a dominant wurtzite (WZ) phase that forms in bare GaAs and in InGaAs/GaAs heterostructure (HS) nanowires (NWs). In both cases, the GaAs luminescence exhibits very narrow emission lines, which persist up to room temperature. At 10 K, the energy of the exciton ground state recombination of GaAs NWs is equal to 1.522-1.524 eV. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 40 publications
0
22
1
Order By: Relevance
“…For integrable models, the eigenvalues are known using Yang-Baxter equations, and one may evaluate Tr A (ρ n A ) explicitly. Generalizing previous results [53], we have evaluated the Rényi entropy (1) for the Forrester-Baxter (FB) Restricted Solid On Solid Model (RSOS) on the square lattice [50]. This model is a lattice realisation of all off-critical minimal models M p,p (ξ), including the non-unitary series.…”
Section: Model Analysismentioning
confidence: 93%
“…For integrable models, the eigenvalues are known using Yang-Baxter equations, and one may evaluate Tr A (ρ n A ) explicitly. Generalizing previous results [53], we have evaluated the Rényi entropy (1) for the Forrester-Baxter (FB) Restricted Solid On Solid Model (RSOS) on the square lattice [50]. This model is a lattice realisation of all off-critical minimal models M p,p (ξ), including the non-unitary series.…”
Section: Model Analysismentioning
confidence: 93%
“…In this case the intensity‐dependent behavior shown Figure b would be compatible with the observation of spatially indirect recombination in the type II aligned ZB‐WZ heterostructure . However, we point out that in the GaAs NWs grown in our laboratory and showing the contemporary presence WZ and ZB, a sharp peak has always been observed in the excitonic energy region . In our Te‐doped samples, instead, no excitonic recombination is longer observed, an indication that the PL changes should be attributed to the incorporation of tellurium.…”
Section: Photoluminescencementioning
confidence: 99%
“…Indeed, so far temperaturedependent optical studies in WZ-phase NWs were restricted to the band gap transition A and did not explore B and C, but in GaAs. 7,39 In ref 39, the T dependence of C was reported but not compared with that of A and B transitions. In ref 7, we found that A and B exhibit a similar band gap thermal reduction.…”
mentioning
confidence: 96%